(Mis)understanding political participation digital practices, new forms of participation and the renewal of democracy - Wimmer, Jeffrey; Winter, Rainer 1960-; Wallner, Cornelia; Oelsner, Karoline (Routledge studies in European communication research and education, 2018)
"The practices of participation and engagement are characterised by complexities and contradictions. All celebratory examples of uses of social media, e.g. in the Arab spring, the Occupy movement or in recent LGBTQ protests, are deeply rooted in human practices. Because of this connection, every case of mediated participation should be perceived as highly contextual and cannot be attributed to one (social) specific media logic, necessitating detailed empirical studies to investigate the different contexts of political and civic engagement. In this volume, the theoretical chapters discuss analytical frameworks that can enrich our understanding of current contexts and practices of mediated participation. The empirical studies explore the implications of the new digital conditions for the ways in which digitally mediated social interactions, practices and environments shape everyday participation, engagement or protest and their subjective as well societal meaning."--Provided by publisher